Examining the barriers to gender integration in agriculture, climate change, food security, and nutrition policies: Guatemalan and Honduran perspectives - Howland, Fanny C.; Acosta, Mariola; Muriel, Juliana; Le Coq, Jean-François (Frontiers Media, 2021)
Gender mainstreaming is seen, at international level, as critical to achieving national development goals and addressing key global challenges such as climate change and food and nutrition insecurity in the agriculture sector. Our study examined the barriers leading to poor gender mainstreaming and potential solutions in policies applying to gender, agriculture, climate change, food security and nutrition, in both Guatemala and Honduras. We used a case study approach to analyze the barriers to gender integration in these governments’ policies. Based on semi-structured interviews and policy document analysis, we conducted a methodology based on policy mix, policy integration and policy translation. Results show that, despite having made multiple international commitments on gender issues and having gender-labeled policy and governmental gender bodies, gender mainstreaming in the policy cycle is lagging. There are multiple barriers of a different nature and at different levels that explain the lack of gender integration in the policy cycle, related and linked to: (1) policy translation from the international level; (2) structural policy barriers at national level; (3) behaviors and corruption; and (4) lack of knowledge and capacity. Solutions to address these barriers have been identified. Our results confirmed the literature findings and also introduce new elements such as the importance of considering the nature of the relationship (purely technical and/or political) between governments and international cooperation actors to evaluate the level of gender integration in policy. Furthermore, we stress that for key informants, there are no (easy) solutions to redress the poor gender integration strategies implemented. Finally, we noted that no solutions were provided relating to structural racism and machismo, religious extremism, power groups, and censorship of civil society.